The feasibility of using landsat TM imagery for longterm vegetation monitoring in the fynbos biome - Kotze, Johann De Flaming (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScNbew) -- University of Stellenbosch, 1999.